Effect of Spacing and Fertilizer Levels on Growth, Yield and Economics of Grain Amaranth (Amaranthus hypochondriacus L.) - Tandle, Shivani Sunil (International Journal of Environment, Agriculture and Biotechnology, 2024)
The present investigation was conducted to estimate the Impact of spacing and fertilizer levels on growth, yield and economics of grain amaranth during rabi season of 2022 at Experimental farm, Agronomy Department, College of Agriculture, Parbhani. The experiment was laid out in split plot design with three replication. Main plots were assigned to the different spacing viz S1: 45cm x 15cm, S2 : 45cm x 20cm and S3 : 30cm x 20cm and subplot comprises of four fertilizer levels viz. F1 : 30:20:10 NPK kg ha-1, F2 :45:30:15 NPK kg ha-1, F3 :60:40:20 NPK kg ha-1 and F4 :75:50:25 NPK kg ha-1. The experimental gross plot size was 5.4 x 4.8 m2 and net plot size varied as per treatment. On 21st November, 2022, sowing was carried out by dibbling the seed @ 2 kg ha-1. The result of experiment revealed that sowing of amaranth at spacing of 45cm ×15cm and application of 75:50:25 NPK Kg ha-1 were found more productive and profitable.